Bactericidal and anti-inflammatory effects of Moquilea tomentosa Benth. flavonoid-rich leaf extract - Mariana Freire Campos; Leopoldo Clemente Baratto; Vinícius Mendes Vidal; Ivana Ventura Nascimento; Brendo Araujo Gomes; Genes de Lima Martins Neto; Priscilla Christina Olsen; Rodrigo Ribeiro Tarjano Leo; Lilian Oliveira Moreira (BMC Complementary Medicine and Therapies, 2023)
Abstract Background Natural products are an important source of bioproducts with pharmacological properties. Here we investigate the components of leaves from M. tomentosa Benth. (Fritsch) (Chrysobalanaceae) and its effects on bacterial cell growth, biofilm production and macrophage activity. Methods The effect of the different leaf extracts against bacterial cell growth was performed using the microdilution method. The most active extract was analyzed by mass spectrometry, and its effect on bacterial biofilm production was evaluated on polystyrene plates. The extract effect on macrophage activity was tested in the RAW264.7 cell line, which was stimulated with different concentrations of the extract in the presence or absence of LPS. Results We show that the ethyl acetate (EtOAc) extract was the most effective against bacterial cell growth. EtOAc extract DI-ESI (-)MSn analysis showed the presence of a glycosylated flavonoid tentatively assigned as myricetin 3-O-xylosyl-rhamnoside (MW 596). Also, the EtOAc extract increased biofilm formation by S. aureus and inhibited cytokine and NO production induced by LPS in RAW macrophages. Conclusion M. tomentosa flavonoid-enriched EtOAc extract presented a bactericidal and anti-inflammatory pharmacological potential.